Comparative study of pomelo‐peel‐derived hydrochar and torrefied poultry‐litter on coal fuel blends: Combustibility, synergy factor, and ash analysis. (18th June 2022) - Xue, Tianjiao; Fakudze, Sandile; Ma, Ru; Han, Jiangang; Chu, Qiulu; Zhou, Peiguo; Chen, Jianqiang
Abstract: Co‐firing is considered to be a promising approach for the reduction of CO2 emissions from coal‐fired plants. However, the utilization of fruit‐waste‐based feedstocks is less common than the use of animal‐waste feedstocks, which are usually accompanied by high toxic ash content and low combustibility. In this work, pomelo‐peel‐derived hydrochar (PPHC), characterized by excellent fuel properties and combustibility, was systematically compared with torrefied poultry litter (PLBC), to promote its use as an eco‐friendly solid fuel. The two bio‐based solid fuels were prepared using hydrothermal carbonization (180–240 °C) and torrefaction (220–310 °C), respectively. Elemental analysis, proximate analysis, scanning electron microscopy, Brunauer–Emmett–Teller (BET) analysis, and Fourier‐transform infrared (FTIR) spectroscopy were used to study the physicochemical and structural properties of the prepared chars. The combustion behavior and post‐combustion ash content of PPHC/coal and PLBC/coal blends were assessed by thermogravimetric analysis (TGA) and X‐ray fluorescence (XRF). Fuel blends of PPHC and coal showed superior combustibility ( S = 5.77–14.79 × 10 −12 ), stronger synergistic effects (1.48–3.19°C −3 min −1/2 ), and lower activation energy requirements (28.5–31.6 kJ mol −1 ), in comparison with PLBC/coal blends. Comparative analysis of heavy metal content revealed that PPHC/coal blends were characterized by less toxicity, with lower concentrations of Fe, Mn, Zn, Cu, As, and Co. Hence, the results demonstrated that pomelo peel hydrochar, with excellent combustibility and environmental friendliness, could serve as a better alternative for co‐firing with coal. Meanwhile, torrefied poultry litter showed undesirable ash properties, suggesting an urgent need for the development of alternative methods for its treatment. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.